In search of a new theory of food (in)security: evidence from Tanzania - Kotchofa, Pacem Arelys Kadjogbe Chantal (Kansas State University, 2019)
Words have meaning, and meanings influence actions and responses. For decades, food insecurity has been increasingly connected to other concepts, primarily hunger, as if they are congruent. A challenge to the congruence of the meaning of these two concepts is the primary motivation for this research. The study hypotheses that if they are, indeed, congruent, then their antecedents would be statistically the same. Moreover, if they were different, there is a need to explain why researchers, policymakers and others have continued to use them interchangeably and what effect that “error” has had on the ability to address problems presented by food insecurity and hunger. To test the hypothesis of congruence, we conducted a systematic review of the literature focusing on the origin, etymology, and mixed-use of both concepts in the context of economic development. We found that while hunger is defined as a sensation or pain that results from the want of food especially after hours of fast, food insecurity, instead, shall be referred to as the lack of security about food. It means worrying or fearing that one may not have food or enough food to eat, which does not include necessarily hunger. We then leveraged the foundational meaning of the concepts from an applied perspective and developed a new interpretation showing that hunger and food insecurity are not synonyms. They may, however, be placed on a continuum that transforms hunger into food insecurity under certain conditions. The study provided an empirical analysis of this transformation using the Living Standards Measurement Survey dataset for Tanzania (2014-2015). For robustness check, a comparison was made with the findings from Tanzania’s previous years’ survey data, i.e., a two-years’ panel (2010-2011) and (2012-2013). The results show that, even though they are related, hunger and food insecurity are not congruent, and treating them as synonyms in policymaking creates measurement hurdles that are already evident in the results from seven decades of attempts to ameliorate food security and address hunger. First, the summary statistics indicate that more than 30% of respondents were food insecure, i.e., “worried about food” even though they were not hungry. Meanwhile, more than 90% of those who were hungry were also food insecure. Next, we reject the null of congruence and conclude that factor explaining household food insecurity were statistically different from those anteceding hunger at a 5% significance level of the Wald test. Finally, we were also able to establish the threshold at a minimum of two days (H ≥ 2), which turned hunger into food insecurity. Beyond two days of hunger, people begin to worry and become food insecure. Based on the foregoing, we recommend, for policy discourse, to acknowledge household hunger continuum and the threshold at which it turned into food insecurity. Besides, to enhance household food security in Tanzania, we argue for the need to strengthen household resilience to shocks leading to food insecurity and hunger such as drought, a massive rise in food prices, and loss of asset ownerships like livestock due to diseases. Similarly, policies that improve their food expenditures and asset ownership, i.e., livestock, poultry, and agricultural equipment, would effectively mitigate the likelihood of food insecurity. The significant contribution of this research to the literature is that hunger may be a contributing factor to household food insecurity but not a sufficient condition, thereby negating the congruence under H < 2 days.
Keywords: Food insecurity; Hunger; Bivariate probit model; Seemingly unrelated models; Tanzania